CORRELATION BETWEEN SERUM URIC ACID LEVELS AND LDL/HDL RATIO IN TYPE II DIABETES MELLITUS – AN OBSERVATIONAL STUDY - DR.KALAISELVI.V.S,; DR.GUNANITHI.K,; DR.MANJULA DEVI.A.J,; DR.MYTHILI.S.V,; DR.SHANTHI.B, (International Journal of Pharma and Bio Sciences, 2014)
Serum uric acid level is associated with the individual components of diabetic metabolic syndrome such as obesity, dyslipidemia. Various components of diabetic dyslipidemia including raised LDL cholesterol, low HDL cholesterol and raised triglycerides were independently associated with hyperuricemia in type II diabetes mellitus. Uric acid increase is observed in individuals with insulin resistance, probably because hyperinsulinemia would cause lower renal uric acid excretion1 Additionally, insulin could indirectly act on uric acid, since there is an association between hyperinsulinemia and hyper triglyceridemia.The association between serum uric acid levels and LDL/HDL cholesterol ratio could pave way for newer therapeutic strategies aimed at serum uric acid levels.This study was done in 60 individuals aged 40-60 years, cases including 30 diabetic individuals ,and controls 30 healthy individuals. The study showed that serum uric acid levels were significantly higher in patients with type II diabetes mellitus than in normal healthy controls . LDL/HDL cholesterol ratio was significantly higher in patients with type II diabetes mellitus.